2008
DOI: 10.1021/jp804140e
|View full text |Cite
|
Sign up to set email alerts
|

Great Influence of Anions for Controllable Synthesis of CeO2 Nanostructures: From Nanorods to Nanocubes

Abstract: Controllable synthesis of well-shaped nanocrystals is of significant importance for understanding the surfacerelated properties as well as for the exploration of potential applications. Herein, CeO 2 nanorods and nanocubes were selectively synthesized using cerium(III) chloride and cerium(III) nitrate as precursor, respectively. Counter anions of the cerium source were crucial to the shapes of the resulting products. Intriguingly, the as-synthesized nanorods could be converted into nanocubes by the addition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
148
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(162 citation statements)
references
References 44 publications
5
148
0
Order By: Relevance
“…Two types of shape-controlled nanoceria supports (nanocubes and nanorods) were prepared according to previously reported methodologies [18,[29][30][31]. For ceria nanocubes (CeO 2 -C) a NaOH solution (57.60 g NaOH dissolved in 210 mL of distilled water) was added dropwise into a Ce(NO 3 ) 3 ·6H 2 O solution (5.21 g of Ce(NO 3 ) 3 ·6H 2 O in 30 mL of distilled water) under vigorous stirring.…”
Section: Catalyst Preparationmentioning
confidence: 99%
“…Two types of shape-controlled nanoceria supports (nanocubes and nanorods) were prepared according to previously reported methodologies [18,[29][30][31]. For ceria nanocubes (CeO 2 -C) a NaOH solution (57.60 g NaOH dissolved in 210 mL of distilled water) was added dropwise into a Ce(NO 3 ) 3 ·6H 2 O solution (5.21 g of Ce(NO 3 ) 3 ·6H 2 O in 30 mL of distilled water) under vigorous stirring.…”
Section: Catalyst Preparationmentioning
confidence: 99%
“…17 Eventually, CeO 2 rods were converted into well-defined CeO 2 polyhedron particles with {200} and {111} facets. The growth rate of {200} appeared to be higher than that of {111}.…”
Section: Kepenekçi Et Almentioning
confidence: 99%
“…The effect of pH on the crystallization of nanosized CeO 2 was studied by Li W-H et al 16 It was claimed that the crystallites synthesized in an acidic hydrothermal medium are larger and more monodisperse than the ones produced in a neutral or alkaline medium. The effect of the counteranions of cerium source on CeO 2 nanostructures was investigated by Hu et al 17 They reported that the synthesized nanorods converted into cubes by addition of NO agent and an oxidizer during the formation of the CeO 2 cubes. The influence of several other anions (such as Br − , I − , and SO 2− 4 ) was also investigated showing that the basicity of the hydrothermal medium had a direct influence on the size and shape of the particles formed.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous CeO 2 synthesis procedures have been reported in literature [10][11][12][13] leading to various nanoparticle morphologies. These materials were extensively studied owing to their many distinctive characteristics and applications such as catalysts in the fuel cell technology [14], gas sensor [15], catalytic wet oxidation [16][17], oxygen storage and release [18], wastewater treatment [19] or photo-catalytic oxidation of water [20].…”
Section: Introductionmentioning
confidence: 99%